Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
We can use substitution.
We can substitute 2x + 3 for 'y' in the 2nd equation.
y = 3x + 5
2x + 3 = 3x + 5
Subtract 3 to both sides:
2x = 3x + 2
Subtract 3x to both sides:
-x = 2
Multiply -1 to both sides:
x = -2
Now we can plug this into any of the two equations to get our y-value:
y = 2x + 3
y = 2(-2) + 3
y = -4 + 3
y = -1
So our solution is (-2, -1)
We can substitute 2x + 3 for 'y' in the 2nd equation.
y = 3x + 5
2x + 3 = 3x + 5
Subtract 3 to both sides:
2x = 3x + 2
Subtract 3x to both sides:
-x = 2
Multiply -1 to both sides:
x = -2
Now we can plug this into any of the two equations to get our y-value:
y = 2x + 3
y = 2(-2) + 3
y = -4 + 3
y = -1
So our solution is (-2, -1)
[tex]y=2x+3\\
y=3x+5\\\\
2x+3=3x+5\\
2x-3x=5-3\\
-x=2\\
x=-2\\\\
y=2\cdot(-2)+3\\
y=-4+3\\
y=-1[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.